Looking for Peyton Place - Delinsky, Barbara (Waterville, Me. : Thorndike Press, 2005)
The death of her mother brings award-winning nonfiction writer Annie Barnes back to the New Hampshire mill town of her youth to investigate the pollution caused by the local paper mill, a contamination that may have been the cause of her mother's fatal illness and that many in the town do not want publicized. 350,000 first printing.
"Thorndike Press large print basic"--T.p. verso
89297
Keywords: City and town life -- Fiction; Paper mills -- Fiction; Pollution -- Fiction; Large type books; New England -- Fiction; Domestic fiction